Sistem Inventory Material Bangunan Berbasis Website di Toko Keramik Jakarta - Kevin; Harfebi Fryonanda (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Toko Keramik Jakarta is a store engaged in materials. In managing Toko Keramik Jakarta's goods which are concentrated in checking the availability of goods, stores need a long time the availability of goods so that it increases efficiency in finding certain store goods. Therefore, in making a system to be able to assist Jakarta ceramics stores in assisting inspectors, to managing the availability of goods in order to facilitate users in managing inventory. The inventory system is based on a web site that lists goods, input suppliers, create users, enter goods, enter goods out to report incoming and outgoing goods. Researchers develop the system using prototypes. The results of this resarch is a new inventory system that has been tested using blackbox testing by the user to find out the functions of the system can be used by Toko Keramik Jakarta.